Alkaline Earth Metal Imido Complexes with Doubly Deprotonated Amidine and β-Diketimine Ligands - Martin, Johannes; Langer, Jens; Elsen, Holger; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
Double deprotonation of the amidine DIPP-N=C(tBu)-NH2 or β-diketimine DIPP-N=C(Me)-C(H)=C(Me)-NH2 (DIPP = 2,6-diisopropylphenyl) with strong benzylcalcium or strontium bases gave metal imido complexes with the anions DIPP-N=C(tBu)-N2– (Am2–) and DIPP-N=C(Me)-C(H)=C(Me)-N2– (BDI2–) which crystallized as tetrameric complexes with typical Ca4N4 or Sr4N4 cubane frameworks. Crystal structures of [(Am)Ca·THF]4, [(BDI)Ca·THF]4 and the first Sr imido complex [(Am)Sr·THF]4 are presented. Calculated geometries of [(Am)Ca·THF]4 and [(BDI)Ca·THF]4 (B3PW91/6-311++G**) are in good agreement with the crystal structures. Also complexes with monoanionic ligands (Am-H)– and (BDI-H)– are reported. Charge delocalization in the ligand backbone is discussed. Ligand–metal bonds are calculated to be circa 90 % ionic; the NPA charges on Ca is circa +1.8. The negative charge on the ligand is delocalized over the ligand backbone but there is still considerable electron density on the terminal N (–1.4). Despite this high negative charge, the reactivity of these complexes is generally low due to the strongly bound cubane core. Reaction of [(Am)Ca·THF]4 with phenyl cyanide gave the [(Am)Ca·PhCN]4, clearly demonstrating its low reactivity. Attempts to break the tetrameric cluster in smaller aggregates by addition of 18-crown-6 led to protonation and isolation of (Am-H)2Ca·(18-crown-6). Reaction of [(Am)Ca·THF]4 with iPrN=C=NiPr gave after addition a complex with a unique amido-guanidinate ligand.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Alkaline earth metals; Amidinates; Density functional calculations; Imido ligands; β-Diketiminates